Ecobrick: Fostering Sustainable Environmental Awareness in Tanjung Baru Village Community - Anggi Widiarni; Sri Purwanti Nasution; M Ridho Syarlisjiswan (Smart Society, 2024)
The objective of this community service project is to enhance sustainable environmental awareness among the residents of Tanjung Baru Village, Merbau Mataram District, South Lampung Regency, through the use of ecobricks. The method used involves a training approach with several stages, including initial discussions and social mapping, problem identification, outreach, practice, and evaluation. A total of 40 residents of Tanjung Baru Village participated in this ecobrick outreach program. Data was collected using pre-tests and post-tests analyzed with a Likert scale. The pre-test results showed that 38.7% of participants had sustainable environmental awareness. After participating in the outreach and hands-on practice, the post-test results showed a significant increase to 70.2%. This improvement indicates the effectiveness of the training in raising sustainable environmental awareness. The study emphasizes the need for more training on renewable energy and environmental sustainability to boost community participation and the effectiveness of future outreach programs. Developing a more structured and sustainable outreach program, along with using more advanced evaluation methods, is essential to measure the long-term impact of these interventions.